Association between hyponatremia and adverse clinical outcomes of heart failure: current evidence based on a systematic review and meta-analysis - Zhao, Wanling; Qin, Jiangwei; Lu, Guoyan; Wang, Yang; Qiao, Lina; Li, Yifei (Frontiers in Cardiovascular Medicine, 2023)
Background Heart failure (HF) is a global health challenge. The perturbations in fluid and electrolyte equilibrium, particularly the compromised sodium balance associated with HF lead to high mortality rates. Hence, elucidating the correlation between serum sodium levels and the prognosis of HF is of paramount importance. This study aimed to conduct a comprehensive meta-analysis to thoroughly investigate the interplay between hyponatremia and the prognostic outlook of individuals with HF. Methods A comprehensive search of bibliographic databases including PubMed, Embase, and the Cochrane Central Register of Controlled Trials was conducted to identify relevant observational studies examining the association between hyponatremia and prognosis of HF. Data extraction, synthesis, and assessment of risk of bias were conducted. Meta-analytic methods, sensitivity analyses, and heterogeneity test were employed as appropriate to synthesize the data. Results A total of 43,316 patients with HF were included spanning 25 selected studies. The pooled data revealed a notable association between hyponatremia and elevated risks across short and long-term mortality of HF. Specifically, hyponatremia was found to significantly increase the likelihood of all-cause mortality (Hazard ratio [HR] = 1.94, 95% confidence interval [CI]: 1.78–2.12); 1-year mortality (HR = 1.67, 95%CI: 1.46–1.90); 30-day mortality (HR = 2.03, 95%CI: 1.73–2.25); cardiac mortality (HR = 2.11, 95%CI: 1.81–2.46); and in-hospital mortality (HR = 1.64, 95%CI: 1.15–2.34). Conclusion Our meta-analysis emphasizes the significant impact of hyponatremia on mortality in the HF patient population, highlighting the critical importance of maintaining stable serum sodium levels in HF management.